Validation of a Liquid Biopsy Protocol for Canine BRAFV595E Variant Detection in Dog Urine and Its Evaluation as a Diagnostic Test Complementary to Cytology - Gentilini, Fabio; Palgrave, Christopher J.; Neta, Michal; Tornago, Raimondo; Furlanello, Tommaso; McKay, Jennifer S.; Sacchini, Federico; Turba, Maria E. (Frontiers in Veterinary Science, 2022)
A significant proportion of canine urothelial carcinomas carry the driver valine to glutamic acid variation (V595E) in BRAF kinase. The detection of V595E may prove suitable to guide molecularly targeted therapies and support non-invasive diagnosis of the urogenital system by means of a liquid biopsy approach using urine. Three cohorts and a control group were included in this multi-step validation study which included setting up a digital PCR assay. This was followed by investigation of preanalytical factors and two alternative PCR techniques on a liquid biopsy protocol. Finally, a blind study using urine as diagnostic sample has been carried out to verify its suitability as diagnostic test to complement cytology. The digital PCR (dPCR) assay proved consistently specific, sensitive, and linear. Using the dPCR assay, the prevalence of V595E in 22 urothelial carcinomas was 90.9%. When compared with histopathology as gold standard in the blind-label cases, the diagnostic accuracy of using the canine BRAF (cBRAF) variation as a surrogate assay against the histologic diagnosis was 85.7% with 92.3% positive predictive value and 80.0% negative predictive value. In all the cases, in which both biopsy tissue and the associated urine were assayed, the findings matched completely. Finally, when combined with urine sediment cytology examination in blind-label cases with clinical suspicion of malignancy, the dPCR assay significantly improved the overall diagnostic accuracy. A liquid biopsy approach on urine using the digital PCR may be a valuable breakthrough in the diagnostic of urothelial carcinomas in dogs.